2019
DOI: 10.11609/jott.4868.11.6.13782-13785
|View full text |Cite
|
Sign up to set email alerts
|

Study of nesting behaviour of Asian Paradise Flycatcher Terpsiphone paradisi (Aves: Passeriformes: Monorchidae) from southern West Bengal, India

Abstract: The Asian Paradise Flycatcher has always been a flamboyant passerine to be photographed quite often throughout the Gangetic Bengal in India, but hardly any behavioural documentation is enlisted till date.  The nesting behaviour of the subject bird encompassing its parental behaviours was studied on a wetland stretch of Ishapore, southern Gangetic Bengal.  The present study mainly deals with the nesting behaviour, incubation activities, hatching, and parental care to fledging of a wild pair.  The behavioural ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…These birds perform an essential role in biocontrol of many insect pests growing in horticulture and agriculture (Thakur et al, 2010). The Asian paradise flycatcher feeds on flies, butterflies, dragonflies, and same behaviour was recorded by Das and Adhikari (2019). Insects were the key source of food for black-winged stilt chicks, with maximum of Diptera (Ueng et al, 2009), with these found in muddy areas.…”
Section: Resultsmentioning
confidence: 62%
“…These birds perform an essential role in biocontrol of many insect pests growing in horticulture and agriculture (Thakur et al, 2010). The Asian paradise flycatcher feeds on flies, butterflies, dragonflies, and same behaviour was recorded by Das and Adhikari (2019). Insects were the key source of food for black-winged stilt chicks, with maximum of Diptera (Ueng et al, 2009), with these found in muddy areas.…”
Section: Resultsmentioning
confidence: 62%
“…Breeding pairs of the species are monogamous, with both males and females actively participating in nesting, hatching, brooding, and feeding of the young (Ngoenjun and Sitasuwan 2009). Although there has been considerable research on the reproductive biology of the species (Mizuta and Yamagishi 1998, Ma et al 2005, Ngoenjun and Sitasuwan 2009, Das and Adhikari 2019, Xi et al 2020, there is relatively little knowledge on its nest-site selection, especially on nest-site variables and their effects on nest survival for the species and even for congeneric species. For example, Currie et al (2003) conducted a comprehensive study in the inner Islands of Seychelles to assess the significance of native broadleaved woodland and wetland areas for the Seychelles Black Paradise Flycatcher (T. corvine).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Casas et al (2016) stated that the vegetation structure and composition offer ideal weather conditions, adequate food resources (fruits and insects), and suitable breeding sites to harbor a wide array of avian populations to perform multiple activities.Foraging guild results demonstrated that Indian paradise ycatchers selected pine trees for perching after sallying. During sallying, they catch insects while ying(Gokula and Vijayan, 2003;Rassussen and Anderton, 2012;Das and Adhikari, 2019), such as ies, bugs, beetles, spiders, moths, butter ies, and damsel ies. The scarlet minivet prefers the tree crown for foraging and perching.…”
mentioning
confidence: 99%